2000
DOI: 10.1034/j.1600-051x.2000.027010769.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses against Porphyromonas gingivalis infection in patients with early‐onset periodontitis

Abstract: These results indicate that EOP patients' antibody response against P. gingivalis infection does not differ significantly from that of AP patients. The person-to-person heterogeneous antibody production against P. gingivalis LPS could contribute to our understanding of the relationship between the defensive ability of EOP patients and their chronic infection with this pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
(51 reference statements)
2
22
0
Order By: Relevance
“…The quantity of antibody has been related to the severity/extent of disease, exacerbations of disease progression, and therapeutic interventions 28,35‐37 . The bacterial specificity of the elevated antibody varies among patients and categories of periodontitis 29,38‐43 . Some recent studies 24,44,45 suggested that the level and isotype of antibody in maternal serum or cord blood, with specificity for individual oral species, is correlated with an increased risk for PTB/LBW deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of antibody has been related to the severity/extent of disease, exacerbations of disease progression, and therapeutic interventions 28,35‐37 . The bacterial specificity of the elevated antibody varies among patients and categories of periodontitis 29,38‐43 . Some recent studies 24,44,45 suggested that the level and isotype of antibody in maternal serum or cord blood, with specificity for individual oral species, is correlated with an increased risk for PTB/LBW deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were extracted by the method of Guo et al (2000). Proteins were extracted by the method of Guo et al (2000).…”
Section: Western Immunoblottingmentioning
confidence: 99%
“…In the present series, however, no specific clinicopathological features characterizing Ag53-specific antibody response were recognized. Kurihara et al (1991) and Guo et al (2000) documented the Western blot detection of antibodies against Ag53 in the serum of 70% of periodontitis patients. In the present study, the antibodies to Ag53 were not detected in the serum with the AlphaScreen method.…”
mentioning
confidence: 99%